Advances in the epidemiology of pancreatic cancer: Trends, risk factors, screening, and prognosis. (1st November 2021) - Cai, Jie; Chen, Hongda; Lu, Ming; Zhang, Yuhan; Lu, Bin; You, Lei; Zhang, Taiping; Dai, Min; Zhao, Yupei
Abstract: Pancreatic cancer is a malignancy with poor prognosis and high mortality. The recent increase in pancreatic cancer incidence and mortality has resulted in an increased number of studies on its epidemiology. This comprehensive and systematic literature review summarizes the advances in the epidemiology of pancreatic cancer, including its epidemiological trends, risk factors, risk prediction models, screening modalities, and prognosis. The risk factors for pancreatic cancers can be categorized as those related to individual characteristics, lifestyle and environment, and disease status. Several prediction models for pancreatic cancer have been developed in populations with new-onset diabetes or a family history of pancreatic cancer; however, these models require further validation. Despite recent progress in pancreatic cancer screening, the quantity and quality of related studies are also unsatisfactory, especially with respect to the identification of high-risk populations and development of effective screening modality. Apart from the populations with familial genetic risk and those at a high risk of sporadic pancreatic cancer, risk factors such as new-onset diabetes may be a new direction for timely intervention. We hope this work will provide new ideas for further prevention and treatment of pancreatic cancer. Highlights: Both incidence and mortality rate of pancreatic cancer has increased in recent years. Risk factors for PDAC include individual characteristics, lifestyle and environment, and disease status. The current established modality for effective early detection of PDAC is lacking. Development of effective biomarkers predicting the prognosis are in high demand.